Mechanical characterizations of high temperature polymer encapsulation - Chan, Wei Hao (2018)
The development of a new high temperature polymer is the key to achieving high reliability operations in aerospace and well-logging applications as conventional encapsulation materials such as epoxy, polyimide or silicone do not suffice in high pressure high temperature (HPHT) environment.